Genetic Platforms of blaCTX-M in Carbapenemase-Producing Strains of K. pneumoniae Isolated in Chile - Carrasco-Anabalón, Sergio; Vera-Leiva, Alejandra; Quezada-Aguiluz, Mario; Morales-Rivera, María F.; Lima, Celia A.; Fernández, Jorge; Ulloa, Soledad; Domínguez, Mariana; González-Rocha, Gerardo; Bello-Toledo, Helia (Frontiers in Microbiology, 2018)
Abstract Objective: To elucidate whether the genetic platforms of blaCTX-M contribute to the phenotypes of multi-drug-resistance in the first carbapenemase-producing K. pneumoniae strains isolated in Chile. Method: Twenty-two carbapenemase-producing K. pneumoniae strains isolated from different Chilean patients and hospitals were studied. Their genetic relatedness was assessed by PFGE and MLST. The levels of antibiotic resistance were evaluated by determining the minimum inhibitory concentration of various antimicrobials. In addition, several antibiotic resistance genes of clinical relevance in Chile were investigated. The prevalence, allelic variants and genetic platforms of blaCTX-M were determined by PCR and sequencing. Results: Out of the twenty two strains studied, twenty carry KPC, one carries NDM-1 and one carries OXA-370. The PFGE analysis showed three clades with a genetic relatedness >85%, two formed by four strains and one by eight strains. The other strains are not genetically related, and a total of seventeen different pulse types were detected. Ten different STs were identified, the main ones being ST258 (five strains) and ST1161 (seven strains). The isolates presented different percentages of resistance, and 82% were resistant to all the β-lactams tested, 91% to ciprofloxacin, 73% to colistin, 59% to gentamicin, 50% to amikacin, and only 9% to tigecycline. All isolates carried blaTEM and blaSHV, whereas 71% carried aac(6’)Ib-cr, and 57% one qnr gene (A, B, C, D or S). The blaCTX-M gene was found in 10 of the isolates (4 blaCTX-M-15 and 6 blaCTX-M-2). The characterization of the platform, in seven selected strains, revealed that the gene is associated with unusual class 1 integrons and insertion sequences such as ISCR1, ISECp1 and IS26. Conclusion: In the first carbapenemase-producing K. pneumoniae strains isolated in Chile the genetic platform of blaCTX-M-2 corresponds to an unusual class 1 integron that can be responsible for the MDR phenotype, whereas the genetic platforms of blaCTX-M-15 are associated with different IS and do not contribute to multi-drug resistance.